Extreme conservation : life at the edges of the world - Berger, Joel (The University of Chicago Press, 2018)
"On the Tibetan Plateau, there are wild yaks with blood cells thinner than those of horses' by half, enabling the endangered yaks to survive at 40 below zero and in the lowest oxygen levels of the mountaintops. But climate change is causing the snow patterns here to shift, and with the snows, the entire ecosystem. Food and water are vaporizing in this warming environment, and these beasts of ice and thin air are extraordinarily ill-equipped for the change. A journey into some of the most forbidding landscapes on earth, [this book] is an eye-opening, steely look at what it takes for animals like these to live at the edges of existence. But more than this, it is a revealing exploration of how climate change and people are affecting even the most far-flung niches of our planet."--Amazon.com summary.